Sirtuins as Regulators of the Yeast Metabolic Network - Ralser, Markus; Michel, Steve; Breitenbach, Michael (Frontiers in Pharmacology, 2012)
There is growing evidence that the metabolic network is an integral regulator of cellular physiology. Dynamic changes in metabolite concentrations, metabolic flux, or network topology act as reporters of biological or environmental signals, and are required for the cell to trigger an appropriate biological reaction. Changes in the metabolic network are recognized by specific sensory macromolecules and translated into a transcriptional or translational response. The protein family of sirtuins, discovered more than 30 years ago as regulators of silent chromatin, seems to fulfill the role of a metabolic sensor during aging and conditions of caloric restriction. NAD+/NADH interconverting metabolic enzymes glyceraldehyde-3- phosphate dehydrogenase and alcohol dehydrogenase, as well as enzymes involved in NAD(H), synthesis provide or deprive NAD+ in close proximity to Sir2. This influence sirtuin activity, and facilitates a dynamic response of the metabolic network to changes in metabolism with effects on physiology and aging. The molecular network downstream Sir2, however, is complex. In just two orders, Sir2’s metabolism-related interactions span half of the yeast proteome, and are connected with virtually every physiological process. Thus, although it is fundamental to analyze single molecular mechanisms, it is at the same time crucial to consider this genome-scale complexity when correlating single molecular events with phenotypes such as aging, cell growth, or stress resistance.